Nicaea 325 – The "Most Important Creed in Ancient Eastern Christianity" - Vinzent, Markus (Religion & theology, 2025)
Nicaea 325 was characterised as "the most important creed in ancient eastern Christianity," according to Hans-Georg Opitz. He contends that the emperor’s imposition of peace on the Church sparked further disputes and deepened the divide between Western and Eastern Churches. Despite the 2025 jubilee commemorating Nicaea’s significance, the lack of historical documentation raises questions about its true impact. Eusebius of Caesarea, the primary source of information regarding the council, is seen as biased, calling into doubt the credibility of the available accounts. Gaps in knowledge, particularly about the creed’s formation, emphasise the inconsistencies in its perceived importance, suggesting a more complex and less understood legacy than commonly believed.